Numerical simulation and experimental research the characteristic at rated guide vane opening on pump-turbine. (July 2018) - Liu, D M; Zhao, Z Y; Guan, Z W
Abstract: The performance of a reversible pump turbine with S-shaped (dQ11 /dn11 >0) characteristics is of great harmful to the transient processes such as start-up and load rejection. When working point transition is required, then process in turbine mode must be fast, efficient and reliable. Especially during load rejection, the pressure increasing at spiral case and negative pressure taking place at draft tube. This phenomenon has great relation with the characteristic curve with pronounced S shape. In this paper, the characteristic curve is improved with runner optimization. And hydraulic performance results are compared with runner geometry parameters changing. The runner optimization is an effective method to solve this problem.